Shanghai School (Haipai): Content of the Concept - I. A. Moshchenko (Научный диалог, 2020)
The article is devoted to the analysis of the content of the literary concept of haipai (Shanghai school). It is pointed out that the term is actively used in modern literary studies in the Chinese language and is a basic concept for the classification of Chinese writers of the twentieth century. The question is raised about the legality of using this term for the analysis of works of art. It is noted that the literary polemic of 1933—1934 “The dispute about the Shanghai and Beijing schools” helps to clarify the meaning of the concept of “haipai”. As a result of the analysis of publications of this period, it is concluded that the term Shanghai school in modern literary practice has a different meaning than what the participants in the discussion put into it. The novelty of the research lies in the fact that for the first time in Russian the literary polemics of 1933—1934 are described in detail using primary sources. As a result of the study, it was concluded that in terms of its content, the term haipai is close to such a descriptive concept in European literary criticism as “decadence”. It sets a certain evaluative paradigm and evokes certain visual and sensory images, but it should be used with caution as a means of literary analysis.